This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Finding the value of y .
x y = y ln x = ⟹ ln x = 3 ln 3 y ln 3
2 x y 4 = x y 4 ln 2 = x y 4 = y 4 ln x = y 4 ln x = y 4 y ln 3 = y 3 ln 3 = y 3 = y = 5 ln 5 ln 2 ln 5 ln ( ln 2 ln 5 ) ln ( ln 5 ) − ln ( ln 2 ) ln ( ln 5 ) − ln ( ln 2 ) ln ( ln 5 ) − ln ( ln 2 ) ln 3 ln ( ln 5 ) − ln ( ln 2 ) 3 ln 3 ln ( ln 5 ) − ln ( ln 2 )
Finding the value of x .
ln x = ⟹ x = x = y ln 3 e raised to y ln 3 e raised to 3 ln 3 ln ( ln 5 ) − ln ( ln 2 ) ln 3
⎩ ⎪ ⎨ ⎪ ⎧ x = 3 . 3 2 1 0 8 5 9 . . . y = 0 . 9 1 5 2 8 7 6 . . . x y = 3 . 0 3 9 7 4 8 . . .
You can use exp ( x ) as a replacement of e x .
Log in to reply
You can use exp ( x ) instead of e x p ( x ) . Just put a '\' in front of the 'exp'.
Problem Loading...
Note Loading...
Set Loading...
2 x y 4 3 y 3 ln 2 3 y 3 y 3 ln 3 y 3 ⟹ y = 2 ( x y ) y 3 = 2 3 y 3 = 5 = ln 5 = ln 2 ln 5 = ln ( ln 2 ln 5 ) = ln 3 ln ( ln 2 ln 5 ) = 3 ln 3 ln ( ln 2 ln 5 ) ≈ 0 . 9 1 5 2 8 7 6 6 7
Since x y = 3 ,
⟹ y ln x ln x x = e y ln 3 ⟹ x y = ln 3 = y ln 3 = y e 3 ln 3 ≈ 0 . 9 1 5 2 8 7 6 6 7 e 0 . 9 1 5 2 8 7 6 6 7 ln 3 ≈ 3 . 0 4